ASSESSMENT OF THE PATTERN OF AGRICULTURAL ACCIDENTS IN A TRIBAL DISTRICT, RATLAM, CENTRAL INDIA - S Kot, Lokendra; K Patidar, Anand; Jain, Anurag; Sharma, Vikash; Gupta, Jitendra; Gupta, Mahesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this study were as follows: (1) Study the various type of agricultural accident in selected district. (2) Study the various factors associated with agricultural accidents. Methods: An observational cross-sectional study conducted after getting ethical approval from ethical committee in villages of Ratlam District selected by stratified random sampling method for the duration of 1 year. Data collected using predesigned structured pro forma through selected villages using key informant approach. Study financially supported by Indian Council of Social Science Research (ICSSR). Discussion: Total 865 were victims of agricultural accidents in our study which include 22.20% (192) females and 77.80% (673) males. Most of the victims (46.24%) who met agricultural accident were from age of 30–45 years and about 6.47% (37 – males and 19 – females) victims were below age of 15 years. Mean age of victims was 32.98 and SD 12.415. Conclusion: Mean ages of victims were 32.98 and SD 12.415. Young workers recorded the highest rate of agricultural injury with 52 accidents per 1000 workers. Incidence of agricultural accidents found to be ≈ 26.11 per 1000 workers per year. Total 865 agricultural injuries were reported, of which 457 (52.83%) by hand tool (Sickle/Pick-axe/hand hoes). The overall accident’s incidence rate calculated was 3.66/1000/year. Sickle accidents were highest which constituted 400(46.24%). The right hand fingers (101) are most affected part followed by the left hand fingers (95).